[OP.LB.02: 06] INVESTIGATION OF URINARY PEPTIDOME OVER PREGNANCY IN RODENT MODEL OF HYPERTENSION. (September 2016) - Samji, S.; Small, H.Y.; Coley, S.; Mischak, H.; Mullen, W.; Delles, C.
Abstract : Objective: Stroke-prone spontaneously hypertensive rats (SHRSP) are a model of chronic hypertension relative to normotensive Wistar-Kyoto rats (WKY). Our studies on urinary protein and electrolyte levels have shown kidney dysfunction and impaired water balance in pregnant SHRSP. We investigated whether urinary peptidomics can identify target molecules involved in kidney dysfunction in pregnant SHRSP. Design and method: We analyzed urine of non-pregnant and pregnant WKY and SHRSP (n = 7) at 0th, 12th and 18th gestational day (GD) using capillary electrophoresis on-line coupled to ESI-TOF-MS. Peptide sequencing was performed in LTQ-Orbitrap™ hybrid mass spectrometer. Quantitative PCR was carried out in kidney specimens of non-pregnant and pregnant WKY and SHRSP (n = 5). Results: The longitudinal comparison within and between WKY and SHRSP at GD0, GD12 and GD18 detected 1228 differentially expressed peptides (p < 0.05, Mann-Whitney test). Repeated measure ANOVA analysis of these peptides identified 46 peptides which were significantly regulated at all time-points and 77 peptides only at GD12 and GD18. In total 43 and 42 peptides markers were down- and up- regulated respectively, at all time-points; while 38 peptides were down-regulated at either, GD12 or GD18 or both, in SHRSP compared to WKY (fold change >1.5, p < 0.05). Peptide sequencing showed fragments of collagen alpha-chains, serum albumin, pro-thrombin, actin, Serpin A3K, pro-epidermal growth factor and uromodulin. Uromodulin peptides showed no significant difference at GD0 while there was 7.8 (p = 0.018) and 8.8 (p = 0.050) fold change increase at GD12 and GD18 respectively, in SHRSP compared to WKY. These results were reflected in mRNA level of uromodulin. No significant change between GD0 and GD18 WKY were identified, while GD0 and GD18 SHRSP showed significant changes (RQ 3.2 ± 0.064, p 0.002 and RQ 6.1 ± 0.048, p 0.0005, respectively). Conclusions: We observed a characteristic peptidomic pattern which was altered in response to both pregnancy and hypertension. Uromodulin is a candidate gene for human hypertension and renal dysfunction but, as yet has not been shown to play a role in hypertensive pregnancy. Our findings suggest that uromodulin may be a novel candidate involved in kidney dysfunction during hypertensive pregnancy.